Developing and Evaluating a Virtual Reality-Based Navigation System for Pre-Sale Housing Sales - Yi-Kai Juan; Hsing-Hung Chen; Hao-Yun Chi (Applied Sciences, 2018)
Virtual reality (VR) technologies have advanced rapidly in the past few years, and many industries have adopted these cutting-edge technologies for diverse applications to improve their industrial competitiveness. VR has also received considerable recognition in the architecture, engineering, and construction industries, because it can potentially reduce project costs, delivery time, and quality risks, by allowing users to experience unbuilt spaces before breaking ground, resolving construction conflicts virtually, and reviewing complex details in immersive environments. In the real estate market, VR can also play an important role in affecting buyers’ housing purchasing decisions, especially for housing markets in Asia, where the pre-sale system is extremely common. Applying VR to the pre-sale housing system is promising, because the concept of pre-sale refers to a strategy adopted by developers that sell housing through agreements on residential units that have not been constructed yet, and VR at this stage could be a useful tool for visual communication in a true-to-scale environment. However, does VR really benefit sales in the housing market? Can clients accept using VR, instead of using traditional materials (i.e., paper-based images and physical models), to navigate and experience housing projects? The objective of this study is to develop a VR-based navigation system for a pre-sale housing project in Taiwan. We invited 30 potential clients to test the system and explore the implications of using it for project navigation. The results reveal that VR enhances the understandings of a project (perceived usefulness) and increases clients’ intention to purchase, while the operation of VR (perceived ease-of-use) is still the major challenge to affect clients’ satisfaction and the developer’s acceptance with respect to applying it to future housing sales.